2016
DOI: 10.1113/jp271056
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of cerebrovascular reactivity in healthy children and young adults assessed with magnetic resonance imaging

Abstract: Key pointsr Cerebrovascular reactivity (CVR) reflects the vasodilatory reserve of cerebral resistance vessels. r Normal development in children is associated with significant changes in blood pressure, cerebral blood flow (CBF) and cerebral oxygen metabolism. Therefore, it stands to reason that CVR will also undergo changes during this period.r The study acquired magnetic resonance imaging measures of CVR and CBF in healthy children and young adults to trace their changes with age.r We found that CVR changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 52 publications
4
61
0
Order By: Relevance
“…However, the combination of low vascular response and signal to noise ratio in the white matter could result in negative CVR values in some voxels. In the literature, healthy young adults are not expected to present with negative CVR values during a CO 2 challenge (Leung et al, 2016), except for in the ventricles and other areas occupied by cerebrospinal fluid (Blockley et al, 2011;Ravi et al, 2016). This has been the case in our own work as well (Chen and Pike, 2010b;Halani et al, 2015).…”
supporting
confidence: 67%
“…However, the combination of low vascular response and signal to noise ratio in the white matter could result in negative CVR values in some voxels. In the literature, healthy young adults are not expected to present with negative CVR values during a CO 2 challenge (Leung et al, 2016), except for in the ventricles and other areas occupied by cerebrospinal fluid (Blockley et al, 2011;Ravi et al, 2016). This has been the case in our own work as well (Chen and Pike, 2010b;Halani et al, 2015).…”
supporting
confidence: 67%
“…Cerebral perfusion is known to be developmentally mediated, and peaks between the ages of 5-10 years (Leung et al 2016). Consequently, these elevations in resting CBF have been linked to a reduced cerebrovascular reserve in response to hypercapnia (Leung et al 2016), though little is known about the response to hypoxia.…”
Section: Cerebral Hemodynamic Responses To Hypoxiamentioning
confidence: 99%
“…Cerebral perfusion is known to be developmentally mediated, and peaks between the ages of 5-10 years (Leung et al 2016). Consequently, these elevations in resting CBF have been linked to a reduced cerebrovascular reserve in response to hypercapnia (Leung et al 2016), though little is known about the response to hypoxia. Under hypobaric hypoxic conditions, an increase in anterior CBF has been observed (indexed by middle and anterior cerebral blood velocity; Gavlak et al 2013).…”
Section: Cerebral Hemodynamic Responses To Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Several studies have yielded similar findings in youth specifically. 9,12 Various youth studies have examined CVR using fMRI, finding impaired CVR in cerebral vasculopathy, 15 infarct areas in childhood stroke, 16 and sickle cell disease, 17 Studies of healthy participants have found gradual increases in CVR up to age 14.7 and thereafter, a negative correlation with age (age 9-30), 18 and lower signal-to-noise ratio in healthy young children compared to healthy young adults. 19 Additionally, our previous study examined regional differences, sex differences, and three modeling techniques for analyzing CVR in a healthy youth sample.…”
Section: Introductionmentioning
confidence: 99%